Strength Analysis of Wheel Stopper Design on Dyno Test Based on Solidwork 2019 Software - Purba, Samuel Julianto; Aryadi, Widya (Jurnal Inovasi Mesin, 2024)
Various innovations have been made in all parts of the world to deal with global warming. One of them is making electric vehicles. One of the things that must be done to keep up with the number of electric vehicle production is to innovate the vehicle 'test' tool. The dyno test is one of the 'test' tools for electric vehicles on two wheels. One of the innovation gaps that can be addressed is creating a wheel stopper design on a new dyno test to speed up production time. The wheel stopper was designed using a hydraulic system with MTEK WC1 UNS J13047 cast alloy steel metal material. The design was done using Autodesk Inventor 2024 and analyzed using Solidwork 2019. Then, the analysis results are compared with the existing wheel stopper design using ASTM A36 steel. It will also determine whether a hydraulic system design can be implemented. The maximum displacement and minimum safety factor results obtained on the hydraulic wheel stopper are 0.1746 mm and 2.5. These results show that the hydraulic wheel stopper design can be implemented